1981
DOI: 10.1111/1523-1747.ep12521107
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Cellular Organization of Human Epidermis

Abstract: Cell alignment in the stratum corneum of frozen sections of specimens of human skin was examined by light microscopy following expansion of the stratum corneum in alkaline buffer. Some degree of ordered structure was found in all specimens examined but considerable variation existed in precision of cell alignment. The typical degree of cell alignment was less precise than that typically observed in experimental animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Various mammalian epidermis shows a regular interdigitation pattern in the SC (Christophers, 1972; Mackenzie et al, 1981), suggesting that the f-TKD cell turnover mechanism governs cell differentiation in mammals. Further investigation on whether this characteristic interdigitation pattern is observed in the SC of other vertebrates, such as amphibians, reptiles and birds, may reveal the general applicability of the f-TKD model to cornified stratified epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Various mammalian epidermis shows a regular interdigitation pattern in the SC (Christophers, 1972; Mackenzie et al, 1981), suggesting that the f-TKD cell turnover mechanism governs cell differentiation in mammals. Further investigation on whether this characteristic interdigitation pattern is observed in the SC of other vertebrates, such as amphibians, reptiles and birds, may reveal the general applicability of the f-TKD model to cornified stratified epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…The en-face view that the system used here generates appears to acquire rather homogeneous SC domains, based on the columnar stacking of corneocytes, where the vertical inter-corneocyte spaces are rather big. By comparison, the horizontal inter-corneocyte spaces are small, also compared to the corneocyte volume 5,22,21,42 ; the overall error through "mixing" of domains should therefore be small. Previously, we demonstrated that the Sodium-Hydrogen-Exchanger 1 (NHE1) plays a key role in establishing the critical acidic SC milieu 2 , and how generating this milieu is of key functional importance in the post-natal adaptation and maturation period of mammalian epidermis 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Still, the physical dimensions of the two-photon focus, or the point-spread function of the microscopic system, limit the resolution and determination of intra-versus extracellular compartments within the SC. Nevertheless, the extracellular domains as present in the en-face view that this system generates should be rather homogeneous, based on the columnar stacking of corneocytes (45)(46)(47)(48), whereas the horizontal inter-corneocyte spaces are small compared with the corneocyte volume; the error based on the assignment of specific compartments should therefore be small.…”
Section: Nhe1 Regulates Epidermal Ph and Barrier Functionmentioning
confidence: 99%